Efficient and steady production of 1 : 2 syngas (CO/H2) by simultaneous electrochemical reduction of CO2 and H2O. Issue 7 (28th January 2021) - Yang, Wei; Zhang, Ji-Hong; Si, Rui; Cao, Li-Ming; Zhong, Di-Chang; Lu, Tong-Bu
Abstract : A guest–host pyrolysis strategy is used to synthesize a Co–C/Nx -based single-site catalyst, featuring excellent electrocatalytic performance for syngas production by electrochemical reduction of CO2 and H2 O (FE nearly 100%, formation rate 1.08 mol g −1 h −1 at 1.0 V vs. RHE). Abstract : Efficient generation of synthetic gas (syngas) through the electrochemical reduction of CO2 and H2 O is a promising route to realize the conversion and storage of electricity. The production of syngas with a controlled CO/H2 ratio is significant for the subsequent preparation of value-added chemicals. Herein, a guest–host pyrolysis strategy is employed to synthesize Co–C/N x -based single-site catalytic materials. The as-prepared materials possess a high graphitic degree of carbon, which supports the rapid electron transport and promotes efficient electrochemical reduction reactions. As a result, these materials can serve as excellent electrocatalysts for the production of syngas by the electrochemical reduction of CO2 and H2 O, which exhibits high production rates and steady CO/H2 ratio (v : v = 1 : 2) at wide-range electrochemical windows. The faradaic efficiency reaches nearly 100%, and the formation rate reaches as high as 1.08 mol g −1 h −1 at 1.0 V vs . RHE.